Thermodynamic study of the leaching of recycled lead with sodium citrate (2018)
Lead batteries represent 60% of the world’s electric storage batteries. Nearly 50% of lead consumption worldwide comes from recycled and reused materials. Currently, pyrometallurgical methods represent more than 90% of the technology for lead recovery; However, these processes are criticized due to the emission of sulfur dioxide due to the decomposition of lead sulphate at elevated temperatures, in addition to the emission of particles. The recovery of lead by the recycling of batteries by hydrometallurgical processes has been investigated as an alternative to pyrometallurgical processes. In the present work, a thermodynamic analysis of lead leaching with sodium citrate was carried out. The thermodynamic analysis was based on the study of three stability diagrams constructed with Medusa® software. Leaching tests were carried out that allowed knowing the system, corroborating the thermodynamic analysis carried out and studying the behavior of the system. The results obtained show that it is possible to extract 100% lead with a concentration of leaching agent of 0.25 M, liquid solid ratio 1:1 and 25 ºC.